The construction of teacher identity: A study of pre-service EFL teachers’ discourse in Khulna - Shaikh, Hasan; Kabir, Md. Shahjahan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Teacher identity is not learned rather it is authored not from manuals, nor methods, but through language, experience, and the delicate art of narrating oneself into being. Professional identity development of 15 pre-service EFL instructors is investigated in this paper. The data were collected through semi-structured interview and interpreted based on positioning theory. The findings of this study demonstrate that participants positioned themselves reflexively as empathetic change agents motivated by social injustices and personal struggles. They resisted traditional grammar-based roles, adopting communicative, student-centered pedagogy. Identity was fluid, developed through classroom practice, mentoring, and social determinants such as class and gender. Strategic language use became salient in self-presentation. Several aspired to future roles as reformers or tech-integrated educators, but some were doubtful because of systemic constraints. Such doubtful responders vacillate between conformity and resistance, exercising agency in reflexive resistance to interactive positioning by peers, managers, and symbolic power of English in Bangladesh. Rather than a linear trajectory, identity is envisioned here as a dynamic dance of self within discourse—contradictory, shifting, and morally invested. Ultimately, this research affirms identity not as a credentialing product in the EFL settings in Bangladesh, but as an ongoing tale being told throughout one’s life in tension with other individuals, contexts, and possibility.